2015
DOI: 10.1016/j.seizure.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes in patients with West syndrome: An outpatient clinical study

Abstract: In this study, 37 (33.9%) patients had severe consequences as a result of WS. The majority of the rest could cope with daily life with varying degrees of assistance. Eight percent of the patients had a normal development. These results draw attention to the two-thirds of patients with WS who have the chance of an acceptable quality of life (QoL) with early diagnosis and therapeutic measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
2
23
0
6
Order By: Relevance
“…Additional study is warranted into the long‐term implications of hypsarrhythmia on neurodevelopment. However, most evidence available now suggests that each patient has his or her own range of potential outcomes, heavily influenced by their underlying etiology, and that rapid and effective treatment of infantile spasms likely improves a given patient's trajectory within that continuum . Data on long‐term developmental outcomes would be a valuable avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional study is warranted into the long‐term implications of hypsarrhythmia on neurodevelopment. However, most evidence available now suggests that each patient has his or her own range of potential outcomes, heavily influenced by their underlying etiology, and that rapid and effective treatment of infantile spasms likely improves a given patient's trajectory within that continuum . Data on long‐term developmental outcomes would be a valuable avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…However, most evidence available now suggests that each patient has his or her own range of potential outcomes, heavily influenced by their underlying etiology, and that rapid and effective treatment of infantile spasms likely improves a given patient's trajectory within that continuum. [28][29][30][31][32] Data on long-term developmental outcomes would be a valuable avenue for future research. We supplement use of an ASD at the time of infantile spasms diagnosis for preexisting epilepsy; while these are likely heavily correlated parameters the significance of "preexisting epilepsy" in this paper should be verified with additional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Age of onset of symptoms varies from 2 months to 2 years and peaks around 5 to 7 months. [6][7][8][9][10] Infantile spasm presents at younger age in symptomatic group compared with cryptogenic/idiopathic group. 7,[9][10][11] There is an additional delay up to 3 months for the initiation of appropriate therapy in most of the centers for organizing diagnostic EEG and referral to specialized clinics.…”
Section: Age Of Presentationmentioning
confidence: 99%
“…7,[9][10][11] There is an additional delay up to 3 months for the initiation of appropriate therapy in most of the centers for organizing diagnostic EEG and referral to specialized clinics. [6][7][8][9][10] Lagae et al 9 had noted a short-lag period attributing for early recognition of spasms. However, Gulati et al 12 described long-lag period of 12 months and observed that the treatment could be initiated at the mean age of 18 months.…”
Section: Age Of Presentationmentioning
confidence: 99%
“…По данным МРТ головного мозга выявлены нормальное состояние головного мозга, диффузное корковое и / или субкортикальное поражение, одностороннее корковое и / или субкортикальное поражение. В статистическую оценку включали возраст начала спазмов и фокальных приступов, пол, наследственность, родственный брак, задержку развития или неврологический дефицит до начала эпилептических приступов, этиологию, характеристику познавательной и двигательной активности во время активной фазы спазмов и при дальнейшем наблюдении, реакцию на лечение и течение эпилепсии при дальнейшем наблюдении [17].…”
unclassified